2023
DOI: 10.1097/prs.0000000000010198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pain Control after Reduction Mammaplasty with Combination Bupivacaine and Dexamethasone Regional Block: A Double-Blind Randomized Controlled Trial (NCT04919317)

Abstract: eduction mammaplasty is the seventh most common plastic surgical procedure performed worldwide, with over 600,000 cases performed in 2019. 1 Despite its prevalence, pain control following this procedure remains a challenge. 2,3 Preemptive analgesia commonly administered by means of a preoperative modified block of the pectoral nerves (PECS II) 4 or a serratus plane block using bupivacaine has been shown to greatly improve postoperative pain and decrease in-hospital narcotic use. 5 Bupivacaine (0.5%) is relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Through a hypothesized inhibitory effect of dexamethasone on nociceptive pain fibers, upregulation of inhibitory potassium channels, and a regional decrease in blood flow to slow the dissipation of an infiltrated anesthetic, the majority of published randomized control trials in the orthopedic, gynecologic, and general surgery literature have demonstrated promising outcomes associated with bupivacaine-dexamethasone mixtures relative to bupivacaine alone, through prolonged durations of analgesia and decreased opioid consumption. 7 A recent study by Taylor et al was the first in plastic surgery to report on use of bupivacaine-dexamethasone blocks, demonstrating significant reductions in postoperative pain in patients undergoing reduction mammaplasty receiving this formulation in pectoralis nerve blocks. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through a hypothesized inhibitory effect of dexamethasone on nociceptive pain fibers, upregulation of inhibitory potassium channels, and a regional decrease in blood flow to slow the dissipation of an infiltrated anesthetic, the majority of published randomized control trials in the orthopedic, gynecologic, and general surgery literature have demonstrated promising outcomes associated with bupivacaine-dexamethasone mixtures relative to bupivacaine alone, through prolonged durations of analgesia and decreased opioid consumption. 7 A recent study by Taylor et al was the first in plastic surgery to report on use of bupivacaine-dexamethasone blocks, demonstrating significant reductions in postoperative pain in patients undergoing reduction mammaplasty receiving this formulation in pectoralis nerve blocks. 7 …”
mentioning
confidence: 99%
“… 7 A recent study by Taylor et al was the first in plastic surgery to report on use of bupivacaine-dexamethasone blocks, demonstrating significant reductions in postoperative pain in patients undergoing reduction mammaplasty receiving this formulation in pectoralis nerve blocks. 7 …”
mentioning
confidence: 99%